Citra Maskulinitas dalam Kumpulan Cerpen Sagra Karya Oka Rusmini - Lestari, Dian Asih; Agustina, Emi; Lubis, Bustanuddin (UNIB Press, 2025)
The representation of masculinity in literary works reflects the social and cultural constructions that shape gender roles and identities within society. The purpose of this study was to analyze the image of masculinity of male characters in the Short Story Collection Sagra by Oka Rusmini. The method used is descriptive qualitative. This study examines the Short Story Collection Sagra by Oka Rusmini using a structural approach. The data in this study are in the form of quotations that describe the masculinity possessed by male characters in the Short Story Collection Sagra. The data collection technique used is literature study. The data analysis technique is carried out by reading, understanding, identifying, analyzing, determining results and making conclusions. The results of the study show that the image of male masculinity in the Sagra Short Story Collection is a caste system, emotionally strong, rich, rational, independent, brave, loving and affectionate, breadwinner, responsible and sexual. Beynon's image of masculinity that was not found in this study was the concept of narcissistic men and metrosexual men. This study provides results that there is a difference between Balinese male masculinity and the concept of masculinity expressed by Beynon. Traits such as violence, and hooliganism, swearing, drinking beer, and making jokes that are considered demeaning to women are considered negative traits that are rejected as attributes of Balinese masculinity. Balinese masculinity emphasizes the existence of harmony or balance between attributes of masculinity and social norms, making traits that are not in line with Balinese customary values ​​and norms not considered masculine attributes. Masculinity oppresses both men and women—men are burdened by societal expectations, while women become objects of domination to reinforce masculine identity.